2019
DOI: 10.1093/biolinnean/blz118
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny and evolution of the sound-generating structures in the infraorder Delphinida (Odontoceti: Delphinida)

Abstract: The ontogeny of the structures involved in sound generation and modulation in dolphins was investigated through a comparison of the soft nasal structures of foetal, perinatal, neonatal and adult specimens of Pontoporiidae, Phocoenidae and Delphinidae. Foetal samples were sectioned at 10 µm in the saggital and coronal planes, and stained for histological examination. Computed tomography and magentic resonance imaging scan series were combined with new data to represent the ontogenetic stages of the three groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(40 citation statements)
references
References 74 publications
1
39
0
Order By: Relevance
“…Most dolphins of the infraorder Delphinida, particularly delphinids, produce broadband sounds (BB) for echolocation (Au, 2000). However, some lineages have independently evolved the ability to produce highly directional (Wei et al, 2019) narrow-band high frequency (NBHF) sounds (Kyhn et al, 2010) has revealed that species with highly directional signals convergently developed distinct head features to achieve increased directionality (Frainer et al, 2019a). However, feeding strategy might also determine sound emission patterns as not only preferred preys might differ between strategies (McCurry et al, 2017), but emitted sounds may also be affected by distinct rostrum morphologies adapted for suction or raptorial feeding (Song et al, 2016;Werth, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most dolphins of the infraorder Delphinida, particularly delphinids, produce broadband sounds (BB) for echolocation (Au, 2000). However, some lineages have independently evolved the ability to produce highly directional (Wei et al, 2019) narrow-band high frequency (NBHF) sounds (Kyhn et al, 2010) has revealed that species with highly directional signals convergently developed distinct head features to achieve increased directionality (Frainer et al, 2019a). However, feeding strategy might also determine sound emission patterns as not only preferred preys might differ between strategies (McCurry et al, 2017), but emitted sounds may also be affected by distinct rostrum morphologies adapted for suction or raptorial feeding (Song et al, 2016;Werth, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The vestibular, accessory, and premaxillary sacs are relatively conservative in the delphinids, with the nasofrontal sac being the most variable portion of the system (Heyning & Mead, 1990). The hypothesis of an ontogenetic anomaly since fetal development should not be discarded, as the development of the respiratory apparatus and sound‐generating structures from delphinids starts during fetal phases (Frainer et al, 2019). Late stages of the fetal development, particularly Carnegies stages C18 to F22, are important for tissue formation around the blowhole of delphinids (Frainer et al, 2019).…”
Section: Figurementioning
confidence: 99%
“…The hypothesis of an ontogenetic anomaly since fetal development should not be discarded, as the development of the respiratory apparatus and sound‐generating structures from delphinids starts during fetal phases (Frainer et al, 2019). Late stages of the fetal development, particularly Carnegies stages C18 to F22, are important for tissue formation around the blowhole of delphinids (Frainer et al, 2019). In this context, an opening of a second blowhole after full development of that apparatus would likely undermine its functionality (Frainer et al, 2019).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, soft tissue morphology is likely to be important in the frequency‐determining mechanism, as the acoustic properties of clicks may be influenced by the morphology of the soft tissues of the sound‐producing organs (Cranford et al 1996, Aroyan et al 2000). Interspecific differences in the melon terminal branch (Amundin 1991, Cranford et al 1996, Frainer et al 2019) and the dense connective tissue that covers the posterior end of the melon observed in Phocoenidae, called the ‘porpoise capsule’ (Huggenberger et al 2009), might be involved in the click frequency‐determining mechanism. In addition, vestibular sacs with many plicae (folds), observed in Phocoena phocoena , Phocoenoides dalli , and Neophocoena phocaenoides , are considered to be involved in the generation of NBHF clicks (Curry 1992, Nakamura 1999).…”
Section: Introductionmentioning
confidence: 99%